Model Callaborative Governance Untuk Perencanaan Desa Berkelanjutan Kabupaten Kampar - Aguswan; Mired, Abdul; Astuti, Widia; Saputra, Trio (LPPM STIA Lancang Kuning Dumai, 2025)
Abstract: Sustainable village planning has become a major focus in Indonesia's national development strategy. The concept aims to create rural communities that are resilient, self-reliant, and able to meet the needs of the current generation without compromising the ability of future generations to meet their own needs. This study aims to produce a governance model for stakeholder collaboration in organising sustainable village planning. The model is designed to facilitate sustainable village planning through a collaborative approach involving various stakeholders and their decision-making and implementation processes. Collaboration in village planning is not just an option, but a necessity to realise sustainable village development and through a collaborative approach villages can optimise potential, overcome challenges, and achieve development goals more effectively. The key to success lies in the commitment of all parties to actively participate and build synergy in the village planning process.